Appropriating english in arab-american counter discourse Susan ABULHAWA's "Mornings in jenin" analysis - OSMANIA, Soumia (University of Mostaganem, 2016)
The new millennium witnesses the emergence of a burgeoning sub-genre of literature known as Arab Anglophone literature. This literature is pioneered by writers of Arab origins. Arab-American women writers in particular discuss certain issues in their narratives among which readjusting the image of the Middle-Eastern culture is of premium importance. This dissertation deals with the linguistic phenomenon of “appropriation” and its implementation in the novel of the Palestinian-American writer Susan Abulhawa ‘Mornings in Jenin’. Through appropriating English, Susan Abulhawa dismantles its standard forms to display some linguistic and cultural features of the Arab and Muslim cultures that were misrepresented in Western literature and, hence, uses her narrative as a counter discourse. The main aim of this study is to explore the strategies of language appropriation and displaying the potential implications they convey. In this vein, this research raises three basic: Firstly, what is meant by appropriation in Arab American writings particularly? Secondly, how does the writer articulate this linguistic strategy on her novel? Thirdly, to what ends does the writer employ the textual strategy of appropriation? To answer these questions, the research is designed into four chapters. The first chapter will highlight the notion of discourse in postcolonial literature, the second will negotiate the issue of hyphenated identities in Arab Anglophone literature, the third will represent the theoretical background and an eclectic approach for analyzing the strategies of appropriation that are assumed to be found in the novel like glossing, untranslation, translation, syntactic fusion and code switching and the fourth chapter will be the practical implementation of the eclectic approach on the novel. The results of this research show that the writer mainly uses glossing and code switching to enhance the cultural and linguistic peculiarities of the Arab and Muslim societies